Stages of intensive training of oral monologue broadcasting of future choreographers (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The problem of students’ monologue speech training is considered in this article. The need of bringing of the monologue speech to automaticity due to exercises is indicated. The reasons of grammatical poorness of specialty utterances are shown. The effectiveness of using speech samples, props and models is proved. While studying monologue speech it is important to stimulate with the help of verbal, visual situations. We considered in this work the exercises in which situational approach to the training of monologue speech are being realized. For intensification of the monologue speech training especially at the beginning technical aids can be used. The article deals with the implementation of new modern of monologue and dialogue speech in the training of university students as an important component of their professional competence which is derived with the help of appropriate organization of studies and use of project methods; the grounding of the suitability and necessity of students’ foreign language communication in the modern conditions of education integration and globalization.Professionally-oriented training has a complex structure that combines knowledge of the foreign-language society and professional-oriented society, as well as the professional competence of a specialist on a subject that is being discussed. Note that the accumulation of this knowledge occurs first of all in the native language, and then expands at the expense of a foreign language. Effective formation of skills and abilities of professional monologue broadcasting of choreographer students is realized on the basis of selected educational situations of professionally oriented learning, which are as close as possible to real situations and subject competence of students.
Keywords: lexical unit; monologue speech; utterance; signal point; grammar model